The insertion of an ancestral gene in Nicotiana tabacum plants reduces free radicals during saline irrigation - Claudia Marissa Calderón Torres; Victoria Abril Mancilla Galván; Miguel Murguía Romero (Czech Journal of Genetics and Plant Breeding)
Transgenic organisms modified with ancestral genes for nitrogen metabolism are rare. Previously, it was reported that genetically modified Nicotiana tabacum with the ARO4 gene of aromatic amino acid synthesis from the yeast Debaryomyces hansenii increases its growth during moderate salt stress. In this investigation, it was explored if the changes in the expression of the gene DhARO4 in Nicotiana tabacum, during saline irrigation, are related to the chlorophyll content and the total reactive oxygen species production. Seedlings of transgenic and wild type Nicotiana tabacum germinated in standard conditions were divided into two irrigation groups, with 100 mM of NaCl and with tap water; and, after 50 days, in the non-senescent adult leaves of the plants, the total chlorophyll a and b and the total chlorophyll content were determined by spectrophotometry and the reactive oxygen species production (*OH, 1O2, H2O2) was quantified by a 2',7'-dichlorodihydrofluorescein assay. The expression of the DhARO4 gene was verified with a salt shock of 100 mM of NaCl for 24 hours in the transgenic and wild type plants in the tap water irrigation group. The DhARO4 gene transcript increased (P < 0.05) in the transgenic plant; meanwhile, the average concentration of chlorophyll a increased (P < 0.05), and the average production of reactive oxygen species decreased (P < 0.05).